2022
DOI: 10.1039/d2cy00048b
|View full text |Cite
|
Sign up to set email alerts
|

PtCu alloy cocatalysts for efficient photocatalytic CO2 reduction into CH4 with 100% selectivity

Abstract: In this paper, PtCu alloys with varying Pt/Cu ratios were deposited onto TiO2 nanocrystals to selectively photoreduce CO2 into CH4. The experimental results show that the appropriate Pt/Cu deposition ratio...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 81 publications
0
18
0
Order By: Relevance
“…However, from a kinetic point of view, the formation of CH 4 , which requires eight electrons, is more difficult than the two-electron reduction of CO 2 to CO. So dynamically it is easier to generate CO. 36,37 We also noticed that no product is detected in the reactor without adding a catalyst, light, CO 2 or water.…”
Section: Resultsmentioning
confidence: 84%
“…However, from a kinetic point of view, the formation of CH 4 , which requires eight electrons, is more difficult than the two-electron reduction of CO 2 to CO. So dynamically it is easier to generate CO. 36,37 We also noticed that no product is detected in the reactor without adding a catalyst, light, CO 2 or water.…”
Section: Resultsmentioning
confidence: 84%
“…In a study by Zhao and colleagues in 2022, the authors investigated the selectivity and mechanism of CRR using photocatalysts loaded with PtCu alloy NPs composed of Pt and Cu [39c] . PtCuNPs/TiO 2 were prepared by the H 2 reduction method.…”
Section: Cocatalyst Used For Photocatalytic Crrmentioning
confidence: 99%
“…In a study by Zhao and colleagues in 2022, the authors investigated the selectivity and mechanism of CRR using photocatalysts loaded with PtCu alloy NPs composed of Pt and Cu. [39c] PtCuNPs/TiO 2 were prepared by the H 2 reduction method. X‐ray photoelectron spectroscopy measurements, STEM measurements, and energy‐dispersive X‐ray spectroscopy measurements confirmed the loading of the alloy NPs, consisting of Pt and Cu, on TiO 2 .…”
Section: Cocatalyst Used For Photocatalytic Crrmentioning
confidence: 99%
“…However, the composition and function of the nanoalloys vary in various specific applications. , Notably, the dissociation of H 2 is also a crucial issue in the photothermal catalytic CO 2 hydrogenation process . The efficient dissociation of H 2 promotes the formation of protonated/hydrated H, which provides H species for activated CO 2 and improves the CO 2 reduction efficiency . It is well known that metal nanoparticles are widely valued for their good ability to dissociate H 2 .…”
Section: Introductionmentioning
confidence: 99%
“…34 The efficient dissociation of H 2 promotes the formation of protonated/hydrated H, which provides H species for activated CO 2 and improves the CO 2 reduction efficiency. 35 It is well known that metal nanoparticles are widely valued for their good ability to dissociate H 2 . 36 Wang et al 27 found that Pt has a high ability to adsorb and dissociate H 2 and is often used as a co-catalyst.…”
Section: ■ Introductionmentioning
confidence: 99%